2017
DOI: 10.1158/1078-0432.ccr-17-0219
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Dosing Improves Preclinical Therapeutic Index of Pyrrolobenzodiazepine-Containing Antibody Drug Conjugates

Abstract: To use preclinical models to identify a dosing schedule that improves tolerability of highly potent pyrrolobenzodiazepine dimers (PBDs) antibody drug conjugates (ADCs) without compromising antitumor activity. A series of dose-fractionation studies were conducted to investigate the pharmacokinetic drivers of safety and efficacy of PBD ADCs in animal models. The exposure-activity relationship was investigated in mouse xenograft models of human prostate cancer, breast cancer, and gastric cancer by comparing antit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…In general, the predominant toxicity in rats treated with PBD ADCs is dose-dependent bone marrow suppression. 19 Similarly, in this study, we observed dosedependent decreases in white blood cell and platelet counts that peaked on day 15 post-dose. Importantly, the degree of bone marrow suppression was similar in animals treated with 2 mg/kg of trastuzumab-C239i-SG3249 and those treated with 4 mg/kg of trastuzumab-Flexmab-SG3710 ( Figure S9).…”
Section: Exploratory Toxicology Study In Ratsupporting
confidence: 77%
See 3 more Smart Citations
“…In general, the predominant toxicity in rats treated with PBD ADCs is dose-dependent bone marrow suppression. 19 Similarly, in this study, we observed dosedependent decreases in white blood cell and platelet counts that peaked on day 15 post-dose. Importantly, the degree of bone marrow suppression was similar in animals treated with 2 mg/kg of trastuzumab-C239i-SG3249 and those treated with 4 mg/kg of trastuzumab-Flexmab-SG3710 ( Figure S9).…”
Section: Exploratory Toxicology Study In Ratsupporting
confidence: 77%
“…Hinrichs and colleagues have further elucidated the importance of balancing anti-tumor activity with tolerability when advancing PBD-based ADCs through the preclinical pipeline. 19 After previous fractionated dosing regimens of ADCs based on tubulininhibitors, the authors used fractionated dosing with the PBDbased ADC 1C1-C239i-SG3249 (anti-EphA2, DAR = 2) at 0.5 mg/ kg and compared the anti-tumor effects to those of single-dose administrations of 1C1-C239i-SG3249 ADC at 1 mg/kg in preclinical models of breast, gastric, and pancreatic cancer. 19 They observed that, although dose-fractionation effectively lowers the highest peak serum drug concentrations, equivalent total exposure was maintained, which improved the tolerability of the PBD-based ADCs while maintaining their anti-tumor activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the success of fractionated dosing schedules with gemtuzumab ozogamicin or inotuzumab ozogamicin suggests that the same approach can be used with other ADCs. Indeed, a preclinical study of ADCs with pyrrolobenzodiazepine (PBD) warheads demonstrated that the in vivo efficacy and area under the concen-tration curve were similar regardless of whether the ADC was delivered as a single dose or as fractionated weekly doses, but that fractionated dosing reduced the plasma concentration of the drug and therefore reduced maximum serum concentration-driven toxicities (38).…”
Section: Clinical Dosing Schedulementioning
confidence: 99%